Tubo-Ovarian Abscesses: Epidemiology and Predictors for Failed Response to Medical Management in an Asian Population - Grace Ming Fen Chan; Yoke Fai Fong; Kai Lyn Ng (Hindawi Limited, 2019)
Pelvic inflammatory disease (PID) complicated by tubo-ovarian abscesses (TOA) has long-term sequelae in women of reproductive age. Consensus on the optimal treatment of TOA remains lacking. Most clinicians utilize antibiotics as a first-line conservative approach, failing which invasive intervention is adopted. Our aim is to identify risk factors predicting failed response to conservative medical management for TOA in an Asian population. A retrospective cohort study of 136 patients admitted to a tertiary hospital in Singapore for TOA between July 2013 and December 2017 was performed. Patients were classified into 2 groups: successful medical treatment with intravenous antibiotics and failed medical treatment requiring invasive intervention. 111 (81.6%) of patients were successfully treated with conservative medical approach using intravenous antibiotics; 25 (18.4%) required invasive intervention having failed medical therapy. Multivariate logistic regression model adjusted for age, ethnicity, C-reactive Protein (CRP), TOA size, and body mass index (BMI) showed the odds ratio (OR) of each centimetre increase in TOA size to be 1.28 (95% confidence interval (CI) 1.03-1.61; P=0.030) and every kg/m2 increase in BMI to be 1.10 (95% CI 1.00-1.21; P=0.040). Failed medical management was predicted by a cutoff of TOA size ≥ 7.4 cm and ≥ BMI 24.9 kg/m2. Patients who failed medical treatment received a mean of 4.0±2.1 days of antibiotics before a decision for invasive intervention was made, with a significantly longer intravenous antibiotic duration (9.4±4.3 versus 3.6±2.2 days; P <0.001) and prolonged hospitalization (10.8± 3.6 versus 4.5 ± 2.0 days; P <0.001) compared to the medical group. Patients with higher BMI and larger TOA size were associated with failed response to conservative medical management in our study population. Early identification of these patients for failed medical therapy is imperative for timely invasive intervention to avoid prolonged hospitalization, antibiotic usage, and patient morbidity.